Process reengineering: the role of a planning methodology and picture archiving and communications system team building...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Carrino JA; Unkel PJ; Shelton P; Johnson TG (Journal of Digital Imaging)
The acquisition of a picture archiving and communications system (PACS) is an opportunity to reengineer business practices and should optimally consider the entire process from image acquisition to communication of results. The purpose of this presentation is to describe the PACS planning methodology used by the Department of Defense (DOD) Joint Imaging Technology Project Office (JITPO), outline the critical procedures for each phase, and review the military experience using this model. The methodology is segmented into four phases: strategic planning, clinical scenario planning, installation planning, and implementation planning. Each is further subdivided based on the specific tasks that need to be accomplished within that phase. By using this method, an institution will have clearly defined program goals, objectives, and PACS requirements before vendors are contacted. The development of an institution-specific PACS requirement should direct the process of proposal comparisons to be based on functionality and exclude unnecessary equipment. This PACS planning methodology is being used at more than eight DOD medical treatment facilities. When properly executed, this methodology facilitates a seamless transition to the electronic environment and contributes to the successful integration of the healthcare enterprise. A crucial component of this methodology is the development of a local PACS planning team to manage all aspects of the process. A plan formulated by the local team is based on input from each department that will be integrating with the PACS. Involving all users in the planning process is paramount for successful implementation. Copyright (c) 1999 by W.B. Saunders Company